The wrath of the academics: Criticisms, applications, and extensions of the supernatural punishment hypothesis - Johnson, D (Taylor and Francis, 2017)
If you thought it was a tough life for religious believers living beneath the constant gaze of an omniscient and omnipresent God, spare a thought for the life of an academic. We spend years painstakingly putting together pieces of work that advance a niche field in tiny incremental steps, only to expose ourselves to the intense scrutiny of eagle-eyed peers whose job it is to pick through everything we say with a fine tooth-comb, ready to strike us down on any and all points. It is thus with some trepidation that I read through the eight commentaries on God is Watching You, fearful of thunderbolts that might strike it down. Of course, along with fear there is always awe. It is a great honour when anyone reads one’s work, and a much greater one when they sit down to carefully critique it. In an age when we are bombarded from dawn to dusk with a blizzard of news, social media, blogs, journals, and new books it is a joy to reach anyone and a pleasure to provoke a response. I am therefore extremely grateful to all of the authors for their commentaries. They are remarkable for their diversity and brilliant ideas. It is thus with some trepidation that I read through the eight commentaries on God is Watching You, fearful of thunderbolts that might strike it down. Of course, along with fear there is always awe. It is a great honour when anyone reads one’s work, and a much greater one when they sit down to carefully critique it. In an age when we are bombarded from dawn to dusk with a blizzard of news, social media, blogs, journals, and new books it is a joy to reach anyone and a pleasure to provoke a response. I am therefore extremely grateful to all of the authors for their commentaries. They are remarkable for their diversity and brilliant ideas.